Job satisfaction in an oncology nursing team - Vagnára Ribeiro da Silva; Luciane de Souza Velasque; Teresa Tonini
ABSTRACT Objective: to identify the level of attributed, perceived and real job satisfaction of oncology nursing professionals and analyze the relationships between the levels of satisfaction among these workers. Method: a descriptive, quantitative cross-sectional study was conducted using the Index of Work Satisfaction (IWS) to evaluate the nursing team, nurses and technicians/auxiliaries. A total of 348 workers answered the questionnaire, of which 216 were fully completed and considered for the IWS calculation. Results: Autonomy was considered the most important item in attributed satisfaction for the nursing team and nurses. Salary was valorized most by the technicians/auxiliaries. For perceived satisfaction, Professional Status was the most important for all workers. Regarding real satisfaction, Interaction was the most important for the nursing team and technicians/auxiliaries; while the nurses valorized Autonomy. The nurses presented the greatest job satisfaction. Conclusion: a discrepancy was observed in job satisfaction among the oncology nurses, indicating the importance of further quantitative research.